Developing an Adult Living Donor Liver Transplant Program in Western Europe: The Rotterdam Experience - Alicia Jane Chorley; Wojciech G. Polak; Khe C. K. Tran; Turkan Terkivatan; Jenny Kissler; Michail Doukas; Caroline Den Hoed; Maarten G. Thomeer; Roy Dwarkasing; Herold Metselaar; Jan N. M. Ijzermans; Robert J. Porte; et al. (Transplant International, 2025)
Liver transplantation (LT) is curative for end stage liver disease. Expanding LT indications with limited deceased donor grafts has created organ shortages. Living donor liver transplant (LDLT) increases available organs. In 2019, we restarted our adult LDLT program. We describe our steps to create a successful LDLT program, and our outcomes. Critical steps of program development included market analysis, creation of protocols based on best care practices and a rigorous education program. Patients and donors were then actively recruited for LDLT. Outcomes were measured as morbidity (≥3 on the Clavien-Dindo grading system) and mortality. Between January 2019 and August 2024, 54 LDLT were performed. 2 (3%) donors experienced grade 3A and 7 (12%) donors experience grade 3B complications. There was no donor mortality. 22 (41%) patients were transplanted for PSC, the average MELD score was 13 (6–32). 35 (65%) patients had Roux-en-Y reconstructions. 25 (46%) complications were experienced in 22 (40%) patients, there were 2 recipient deaths. Patient and graft survival after LDLT was 97% and 97%, respectively. This paper reported the successful establishment of a LDLT program in the Netherlands. Establishing a LDLT program brings its own unique challenges, with careful planning and persistence, these challenges can be overcome.